Sociological characteristics of the current state of the laboratory phase of providing dental orthopedic treatment to the population (on the example of the Irkutsk Region) - N. O. Fedchishin; I. S. Kitsul (Acta Biomedica Scientifica, 2016)
Key problems of the dental laboratories in public health sector include insufficient material and technical equipment, weakly theoretically and practically trained personnel and often a mismatch between the structure and organization of the laboratories themselves and modern requirements. To improve the functioning of the dental service, the actual problem remains the laboratory phase of providing dental orthopedic treatment to the population, which has an extremely important medical and organizational value in the quality assurance of orthopedic treatment and achievement of optimalfinal result. Until not distributed modern technology, they are not accessible to the majority of the population. Low competition in the field of high-tech prosthetics causes a high cost. The lag in manufacturing technologies and professional development leads to lowering the quality of public assistance, often inefficient and low-quality dental prosthetics, further enhances the problem, increases the level of need in dental orthopedic care for most of the population using the services of the state dentistry.